Content of child’s world-view and determinants - Zulumskytė, Aušrinė (Acta Paedagogica Vilnensia, 1998)
In this article a concept world-view characterizing the child’s world outlook is discussed, its content is investigated, also significance, determinants for child’s world-view. A diagram of mutual dependence and statement of such determinants is presented. A work is based on analysis and metaanalysis of literature sources. Evaluating the world-view like the childhood stage of world outlook, and our material could be a basis for comparative analysis of integrated and professional systems (programs) of the world recognition in primary school, it could help to look for a ways for successful expansion of child’s world-view and for criterions of the world-view expression.